The - Cullerne, John P. (Oxford University Press, 2008)
This book introduces physics to a first year undergraduate in the language of mathematics. As such it aims to give a mathematical foundation to the physics taught at school as well as extending it to the skills and disciplines approached during a first degree course in physical science or engineering. It bridges two gaps in modern education - between the level of difficulty between A-level and undergraduate study, and between mathematics and physics. Many of the concepts are revised or introduced in the course of 'workshop' questions which are an integral part of the text. Fully explained solutions to these workshops are given as a substantial appendix to the book